Enhancing the Role of Cooperatives in Achieving Community Welfare in Tunah Village, Semanding Sub-district, Tuban - Supratiwi, Wiwik; Agustia, Dian; Soewarno, Noorlailie; Isnalita,; Iswati, Sri; Tjaraka, Heru; Kurniawati, Ika Atma; Kalanjati, Devi Sulistyo; Utama, Anak Agung Gde Satia; Izzato Millati, (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This project aims to strengthen the capacity of the Tunah Village community in managing cooperatives and local natural products such as Siwalan, Legen, or Lontar. It addresses the lack of financial and managerial skills, which limits economic development in the region. Method: Conducted by the Department of Accounting at Airlangga University with PT. Legend Trend, the project involved training sessions in financial accounting, management accounting, and taxation. Data was gathered through observations and pre/post-training assessments. Practical Application: The program provides practical skills for cooperative management and business planning, supporting job creation and economic growth. It aligns with SDG Goal 1 (No Poverty) and Goal 8 (Decent Work and Economic Growth). Conclusion: The project has demonstrated that targeted training in financial and management skills can significantly improve the operational effectiveness of rural cooperatives and unlock the economic potential of natural resources such as Siwalan. These findings highlight the importance of integrated community-university-industry partnerships in fostering sustainable rural development and economic resilience.